Cryogenic insulation performance of polyimide foam-filled fluted-core composite sandwich panels - Li, Xinyu (2024)
Foam-filled composite sandwich structures have demonstrated superior thermal insulation performance, making them highly suitable for cryogenic tanks in launch vehicles. This study focused on the cryogenic insulation characteristics of carbon fiber-reinforced plastic (CFRP) fluted-core sandwich panels filled with polyimide foam. The fluted-core sandwich panel was simplified into a homogeneous multilayer plate to establish a one-dimensional heat transfer theoretical model. This model was used to predict steady-state temperature approximate solutions by linearizing the temperature-dependent thermal conductivity. The sandwich specimens were fabricated using an integrated forming co-cured method. Self-developed cryogenic insulation experiment and finite element simulations were conducted to acquire temperature distributions and validated the precision of the theoretical model. Results showed that the specimens achieved insulation temperature difference exceeding 143.05 °C, with effective thermal conductivity reaching 0.0326 W/(m·°C), significantly lower than that of CFRP. The temperature distributions along the thickness direction displayed a nonlinear increasing trend. The cryogenic thermal short effect was noticeable at the junction of the bottom facesheet and web. An analysis of geometric parameter influences revealed that increasing the short span, core height, or reducing web thickness could enhance thermal insulation characteristics with minimum effective thermal conductivity of 0.0276 W/(m·°C) and lead to a more uniform distribution of bottom temperatures with minimum temperature difference of 3.30 °C. These findings provide a foundational analysis for designing cryogenic insulation structures.